Alan William Cuthbert. 7 May 1932—27 August 2016. (20th June 2020) - Edwardson, J. Michael
Abstract : Alan Cuthbert carried out ground-breaking work on epithelial ion transport. He used radiolabelled amiloride and benzamil to measure the sodium channel density in epithelia from frog skin and toad bladder, tissues that are good models for the distal section of the mammalian kidney tubule. This work shed important new light on how the properties of these channels are modified by hormones such as aldosterone and antidiuretic hormone, and increased our understanding of how diuretics affect kidney function. Later, he focused on the ion transport deficits that underlie cystic fibrosis (CF), and was a member of the team that showed that the ion transport defect could be corrected in CF transgenic mice by gene therapy. Alan was Sheild Professor of Pharmacology and Head of the Department of Pharmacology at the University of Cambridge from 1979 until his retirement in 1999. During this time he was instrumental in moving the Department from the Addenbrooke's Hospital site to a new building in the centre of town. He was also Master of Fitzwilliam College from 1991 until 1999. Alan made major contributions to pharmacology nationally and internationally, serving as chairman of the editorial board of the British Journal of Pharmacology for eight years, and as President of the Federation of European Pharmacological Societies for two years. In recognition of his contributions to the subject, the British Pharmacological Society awarded him their Wellcome Gold Medal in 2005. After his retirement, he continued his research in the Department of Medicine, pursuing novel pharmacological approaches to the treatment of CF.